2011
DOI: 10.1016/j.cpr.2011.01.006
|View full text |Cite
|
Sign up to set email alerts
|

Prospective association of childhood attention-deficit/hyperactivity disorder (ADHD) and substance use and abuse/dependence: A meta-analytic review

Abstract: Given the clinical and public health significance of substance disorders and the need to identify their early risk factors, we examined the association of childhood attention-deficit/hyperactivity disorder (ADHD) with substance use (e.g., nicotine, alcohol) and abuse/dependence outcomes (nicotine, alcohol, marijuana, cocaine, other). To strengthen a potential causal inference, we meta-analyzed longitudinal studies that prospectively followed children with and without ADHD into adolescence or adulthood. Childre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

44
569
9
19

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 720 publications
(641 citation statements)
references
References 117 publications
(116 reference statements)
44
569
9
19
Order By: Relevance
“…Two meta‐analyses, by Charach and Lee 82, 83, have concluded that children diagnosed with ADHD have a higher risk for developing substance use disorders than children without ADHD. The results from this study support previous findings, but in contrast to the Lee study, which could not identify any significant gender interaction effects, our data supports the existence of a sex difference.…”
Section: Discussionmentioning
confidence: 99%
“…Two meta‐analyses, by Charach and Lee 82, 83, have concluded that children diagnosed with ADHD have a higher risk for developing substance use disorders than children without ADHD. The results from this study support previous findings, but in contrast to the Lee study, which could not identify any significant gender interaction effects, our data supports the existence of a sex difference.…”
Section: Discussionmentioning
confidence: 99%
“…The mental health of non-dependent frequent cannabis users was better than expected from studies of all (including dependent) frequent users [3,[10][11][12][13][14][15][16]20]: although mental disorders were more common in non-dependent users than in the general population (OR = 5.35, P < 0.001), this was largely attributable to (childhood) externalizing disorders (OR = 8.91, P < 0.001), whereas there was no difference in the presence of internalizing disorders. Dependent D+ frequent cannabis users with 12-month diagnosis of cannabis dependence (n = 252); D-frequent cannabis users who have never fulfilled criteria for cannabis dependence (n = 269); N2 non-users and non-frequent users in the general population (n = 1072).…”
Section: Discussionmentioning
confidence: 99%
“…More robust associations were found between externalizing disorders and both cannabis use and dependence, especially with regard to attention deficit and hyperactivity disorder (ADHD) and conduct disorder (CD) [12,14,20,21]. Nevertheless, as general population studies either investigate frequency of use or dependence, a direct comparison between frequent cannabis users with and without dependence is lacking.…”
Section: Introductionmentioning
confidence: 99%
“…For example, compared to their peers, adolescents with ADHD experience higher rates of family conflict (Deault 2010), peer problems (Gardner and Gerdes 2013), academic failure (DuPaul and Langberg 2014), comorbid mental health problems (Larson et al 2011), substance use (Lee et al 2011), and driving citations/crashes (Barkley et al 1996). As discussed above, sleep is also related to each of these functioning domains.…”
Section: Applying a Biopsychosocial And Contextual Model To The Studymentioning
confidence: 99%